(untitled) (Nexo Revista Científica, 2021)
The objective was to determine the variability of the concentration of bioactive compounds in six samples of quinoa from Peru. The varieties ‘Blanca de Junín’, ‘Amarillo Maranganí’, ‘Pasankalla’, ‘Altiplano Lima’, ‘Negra Collana’, ‘Altiplano Puno’, which were provided by INIA, were evaluated. The selected samples were cooked (250g/500 ml of distilled water) for 30 min. Significant differences were observed by variety, condition, and the intersection of both by analysis of variance. Regarding the content of phenolic compounds, a significant difference was noted by variety: ‘Amarillo Maranganí’ had the maximum average (2.1287 GAE mg/g). There was a significant difference in antioxidant activity by variety: ‘Negra Collana’ had the maximum average (0.5161 mg GAE/g). There was also a significant difference in flavonoids by variety: ‘Altiplano Puno’ had the maximum average (0.6439 mg/g). For betacyanins there was a significant difference by variety and condition. ‘Altiplano Puno’ had a maximum average (0.5717 mg/100g), being different by variety, condition and both. Finally, ‘Altiplano Puno’ had the highest betaxanthin average (2.1125 mg/100g). Finally, there is evidence to affirm that cooking had an effect on the content of bioactive compounds, being significantly different in the evaluated varieties of quinoa.